The joint strength of glass fibre reinforces plastic (GFRP) tube under internel pressure [compact disc] - Mohd. Yunus Yusof, 1982- (Skudai : Universiti Teknologi Malaysia, 2006)
Project Paper (Sarjana Muda Kejuruteraan (Mekanikal)) - Universiti Teknologi Malaysia, 2006